Extraction of heavy metals from MSWI fly ash using hydrochloric acid and sodium chloride solution. (June 2018) - Weibel, Gisela; Eggenberger, Urs; Kulik, Dmitrii A.; Hummel, Wolfgang; Schlumberger, Stefan; Klink, Waldemar; Fisch, Martin; Mäder, Urs K.
Highlights: Laboratory study of fly ash leaching using HCl 5% and NaCl-solution (300 g/L). Mobilization of Pb and Cu mainly dependent from redox conditions and metal-chloride-complex formation. Thermodynamic modelling used to determine speciation of Pb, Cu, Zn and Cd in leaching solutions. Results of this study indicate a way forward for an improved metal depletion and recovery from fly ash. Abstract: Fly ash from municipal solid waste incineration contains a large potential for recyclable metals such as Zn, Pb, Cu and Cd. The Swiss Waste Ordinance prescribes the treatment of fly ash and recovery of metals to be implemented by 2021. More than 60% of the fly ash in Switzerland is acid leached according to the FLUWA process, which provides the basis for metal recovery. The investigation and optimization of the FLUWA process is of increasing interest and an industrial solution for direct metal recovery within Switzerland is in development. With this work, a detailed laboratory study on different filter cakes from fly ash leaching using HCl 5% (represents the FLUWA process) and concentrated sodium chloride solution (300 g/L) is described. This two-step leaching of fly ash is an efficient combination for the mobilization of a high percentage of heavy metals from fly ash (Pb, Cd ≥ 90% and Cu, Zn 70–80%). The depletion of these metals is mainly due to a combination of redox reaction and metal-chloride-complex formation. The results indicate a way forward for an improved metal depletion and recovery from fly ash that has potential for application at industrial scale.